38th AIAA/ASME/SAE/ASEE Joint Propulsion Conference &Amp;amp; Exhibit 2002
DOI: 10.2514/6.2002-3877
|View full text |Cite
|
Sign up to set email alerts
|

Review of Experiments on Ignition and Flameholding in Supersonic Flow

Abstract: Supersonic combustion data obtained at the low static temperatures appropriate for an efficient scramjet engine are reviewed. Attention is directed at the methods by which the fuel was ignited and combustion maintained. The cited supersonic combustion experiments are grouped under the six headings: chemical intiators; non-uniform flows; turbulent flameholding; combustion induced compression; partial subsonic combustion and plasma sources. The paper is drawn from the NATO RTO AVT WG10 report on technologies for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…It is also well known that the stability of a combustion system has sensitivities due to the chemical content of the test medium. 15,16 Brabbs et. al., 17 showed that under ideal circumstances, vitiated contaminants can cause a change in ignition delay, leading to erroneous conclusions for the flight performance and operability in air.…”
Section: Rbcc Combustor Research Objectivesmentioning
confidence: 99%
“…It is also well known that the stability of a combustion system has sensitivities due to the chemical content of the test medium. 15,16 Brabbs et. al., 17 showed that under ideal circumstances, vitiated contaminants can cause a change in ignition delay, leading to erroneous conclusions for the flight performance and operability in air.…”
Section: Rbcc Combustor Research Objectivesmentioning
confidence: 99%
“…To ignite the room temperature kerosene in the early flight stage, various kinds of methods, including the torch ignition, pilot hydrogen ignition [8,9], choking ignition, etc., have been suggested [10]. Nevertheless, all of these methods need complex operation systems, which will be an extra burden for the scramjet vehicle.…”
Section: Introductionmentioning
confidence: 98%
“…Even if the axisymmetric coflow configuration seems to be very simple, an accurate simulation of this lifted flame is quite demanding. The disadvantage of this and many other scramjet experiments is that the air inflow temperature is relatively high [40]. Hence, with respect to the reaction mechanism the inflow conditions are not the most critical ones that can appear in a scramjet combustor.…”
Section: Turbulent Supersonic Combustion Test Casementioning
confidence: 99%